Canadian parents' knowledge and satisfaction regarding their child's day-care experience. (June 2013) - Howe, Nina; Jacobs, Ellen; Vukelich, Goranka; Recchia, Holly
The purpose of this study was to examine parental selection criteria and satisfaction with day care, knowledge about centre philosophy, teacher education and quality of the day-care environment. Parents ( n = 261) and educators ( n = 94) in 44 non-profit centres in three Canadian cities participated. Parent knowledge was assessed by phone interview, and day-care quality was rated. Many parents reported knowledge of the centre's philosophy and were highly satisfied with the care but sometimes held inaccurate views of the teacher's education. Parent education positively predicted parental knowledge of centre philosophy, while a trend was evident between parent knowledge of centre philosophy and the quality of the day-care environment (i.e. educator–child interaction), after accounting for site effects. Given that parent knowledge about their child's day-care experience may sometimes be incomplete, more frequent and informative parent–educator communication is required, particularly about children's learning and development.